COMMUNITY-BASED DIGITAL MARKETING EMPOWERMENT: A HOLISTIC STRATEGY FOR EMPOWERING RURAL WOMEN MSMES IN SOUTHEAST ASIA - Endang Styawati; Eka Rahayuningsih (Jurnal Ekonomi dan Manajemen, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have significantly contributed to the development of digitalization, which has spurred economic growth globally, including in Southeast Asia. However, Why rural women-led MSMEs face considerable challenges, such as limited digital literacy, the double burden of work and domestic responsibilities, and restricted access to the digital ecosystem. This study aims to develop a comprehensive community-based strategy to support village women's MSMEs through digital marketing. The article presents a conceptual model for "Community-Based Digital Marketing Empowerment." This strategy integrates technology, gender empowerment, and social sustainability, transcending disciplinary boundaries. Employing a qualitative approach, the study includes case studies from Jono Village in Sugihwaras District and Bojonegoro Regency, alongside a review of relevant Southeast Asian literature and data gathered from in-depth interviews and literature reviews. The findings suggest that community-based approaches can enhance the competitiveness of MSMEs while fostering social cohesion through collaboration, collective digital capacity building, and the incorporation of local values. This model aims to contribute to global literature on the digitalization of MSMEs and promote humanitarian values in the digital age.